Smart healthcare application in military medical services - Wang Fan; Hu Lianghao (生物医学转化, 2022)
With the gradual deepening of the Internet of things, big data, cloud computing, artificial intelligence and other information technologies in the medical field, the scientific and technological revolution in the medical industry has reached a climax, promoting the transformation of the traditional medical model to an efficient, comprehensive, convenient and intelligent medical service guarantee system. As a special group, the military officers and men are in a complex and special environment when carrying out all kinds of peacetime, wartime and non war military operations and are often far away from the medical support center. It is more necessary to strengthen the military medical service force through the construction of smart healthcare service. Building a perfect intelligent medical military service support system can improve the combat effectiveness of the army. This paper summarizes the development status of intelligent medicine in recent years, and expounds the application of intelligent medicine in a variety of special military environments such as peacetime, wartime and non war military operations.